Turkey : Request for Stand-By Arrangement and Extension of Repurchase Expectations; Staff Report; Staff Supplements; Press Release on the Executive Board Discussion; and Statement by the Executive Director for Turkey. - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 2005)
This paper discusses Turkey's Request for Stand-By Arrangement (SBA) and Extension of Repurchase Expectations. Turkey's economic program has delivered impressive results. Output has grown rapidly, inflation has fallen to its lowest level in a generation, and government debt has declined markedly. However, significant vulnerabilities remain. The authorities have prepared a three-year economic program for which they are seeking the support of the IMF. Implemented successfully, the program should help Turkey converge toward the economies of the European Union and exit successfully from IMF financial support.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet